Pemberdayaan Potensi Lahan Kosong Desa Wisata Kampung Santan untuk Kemandirian Ekonomi Berkelanjutan - Agung, Langgeng; Jati, Anisa Ambar; Saripudin, Khansa Syaima Rihaadatul Aisya; Puspita, Afifah Lingga; Fahmi, Muhammad Zaki; Sudibyo, Sudibyo; Pramudya, Injira Rizqy; Zalianty, Sebila Aulia; Wahyuni, Sri Amelia; Ramdhani, Aditya Dwi; Ramadhan, Cahyo Setiadi (Universitas Muhammadiyah Yogyakarta, 2025)
The Community Service Program (KKN) of Universitas Muhammadiyah Yogyakarta in Dukuh Santan focuses on optimizing local potential to support sustainable economic independence. One of the main issues faced by the community is the underutilization of vacant land and the lack of innovation in developing the agricultural and tourism sectors. Therefore, this program aims to empower the community through the application of sustainable agricultural technology using demonstration plots (demplots) and digital marketing strategies to enhance the village’s economic and tourism appeal. The methods used include observation, socialization, training, and direct assistance to the community, particularly members of the Women's Farmer Group (KWT). The activities carried out include the establishment of agricultural demplots using a permaculture approach and training on eco-friendly farming techniques. The program results indicate an increased understanding of sustainable farming techniques among the community, the development of a more productive organic farming system, and improved skills among local entrepreneurs in marketing their products. Additionally, the integration of the agricultural sector with Dukuh Santan’s tourism potential has begun to develop through innovations in agricultural products with higher market value. The success of this program is expected to serve as a model for other villages in optimizing their resources to achieve economic independence and strengthen the local tourism sector